High level non-carbapenemase carbapenem resistance by overlaying mutations of mexR, oprD, and ftsI in Pseudomonas aeruginosa - Yan Yang; Xue Li; Lang Sun; Xiu-Kun Wang; You-Wen Zhang; Jing Pang; Guo-Qing Li; Xin-Xin Hu; Tong-Ying Nie; Xin-Yi Yang; Jian-Hua Liu; Gerrit Brandis; et al. (Microbiology Spectrum, 2025)
ABSTRACT Carbapenem-resistant Pseudomonas aeruginosa (CRPA) is a global threat, but the mechanism of non-carbapenemase carbapenem resistance is still unclear. In the current study, we investigated the contributions of point mutations in mexR, oprD, and ftsI to carbapenem resistance in P. aeruginosa during in vivo evolution studies with consecutive clinical isolates. Real-time qPCR and Electrophoretic Mobility Shift Assay demonstrated that MexR (Gln55Pro) mutation increased MexAB efflux pump genes expression by altering MexR’s binding capacity, leading to a four- to eight-fold increase in meropenem MIC in the Pae d1 Green ∆mexR and PAO1∆mexR mutants. The OprD (Trp415*) truncation affected porin structure, and the constructed mutant Pae d1 Green oprD Trp415* increased meropenem MIC by 16-fold (from 0.25 to 4 µg/mL). The contribution of ftsI mutation to meropenem resistance was confirmed by clinical linkage analysis and was estimated to cause a two-fold increase in meropenem MIC by comparing the resistant clinical isolate with the Pae d1 Green oprD Trp415*∆mexR double mutant. The study found that the oprD Trp415* allele alone accounts for the imipenem MIC in clinical isolates, while the ∆mexR and ftsI Arg504Cys alleles do not contribute to imipenem resistance. In conclusion, we identified and explored the contributions of mexR, oprD, and ftsI mutations to high level non-carbapenemase carbapenem resistance in P. aeruginosa. These findings highlight the interplay of different mutations in causing non-carbapenemase carbapenem-resistance in P. aeruginosa.IMPORTANCEThe emergence of carbapenem-resistant Pseudomonas aeruginosa (CRPA) poses a significant global health threat, complicating treatment options for infections caused by this pathogen. Understanding the mechanisms behind non-carbapenemase carbapenem resistance is critical for developing effective therapeutic strategies. This study provides crucial insights into how specific point mutations in key genes-mexR, oprD, and ftsI-contribute to carbapenem resistance, particularly the MexR (Gln55Pro) mutation’s effect on efflux pump expression and the OprD (Trp415*) truncation’s impact on porin structure. The findings elucidate the complex interplay of these mutations, highlighting their roles in conferring high-level resistance, and underscore the imperative for continued research to inform therapeutic strategies against CRPA infections.